(untitled) (INNOVATIVE ECONOMY, 2022)
Gruzina I.А., Pererva I.M. GENERALIZATION OF SCIENTIFIC VIEWS ON THE INTERPRETATION OF THE ESSENCE AND CONTENT OF THE CONCEPT “ORGANIZATION” Purpose. The aim of the article is generalization and systematization of scientific approaches to the interpretation of the concept of “organization” in order to understand its essence, content, patterns of functioning and development. Methodology of research. To achieve this goal, the following methods were used: a systematic approach – to summarize the main views of the authors on this issue; analytical – when working on literary and Internet sources; comparative – to compare the positions of the authors on the issues under study; graphic – for visual presentation of research results. Findings. It is proved that the diversity of scientific ideas and schools that study organizations is due to the peculiarities of the process of forming the theoretical basis for building an organization that took place at the intersection of different fields of knowledge – management, sociology, psychology and many others. There is a lack of a comprehensive theory that could fully explain all existing species, types and forms of organizational structures, to determine the processes that take place in them. There is some confusion in the interpretation and understanding of the term due to the ambiguity and versatility of the concept of “organization” as an object of study, the existence of different, sometimes contradictory, scientific approaches and tools to determine its content. The necessity of research of the organization in statics is as some integral formation, and in dynamics – as various processes on ordering of an element is proved. The distribution of views of scientists to study the organization as: groups of people – 37%, systems – 32%, processes – 18%, functions – 9%, states, phenomena, structures, ideas – 4% among the total number of researched scientific sources. Based on these results, the expediency of combining groups of the organization as a process and function into one general group is substantiated, because the function, in most cases, is considered as a consistent implementation of certain steps (actions, stages), i.e. as a process. This led to a regrouping of definitions of the organization in scientific sources: the organization as a system, including social – almost 69% of definitions; organization as a process – about 27%; organization as a state, phenomenon, structure or idea – about 4%. Originality. There was a further development of generalization of scientific approaches to the study of organizations, according to which almost 70% of professionals consider the organization as a system, which allowed to substantiate the need to use for its study the tools of a systems approach, which is a universal research method. Given that the organization, as the object of study, is a multifaceted category, the need to apply an integrated approach, which, in turn, is one of the main methodological principles of the systems approach. It is proved that this will allow through further research of the structure and basic elements of organizations, their characteristics, features and parameters, as well as functions, principles of operation and laws of behaviour, to systematize and classify organizations by a number of common features and develop effective management method. Practical value. The practical recommendations of the authors on the study of organizations through an integrated approach can be used to identify features of the construction and operation of modern organizations and develop effective methods of managing them. Key words: organization, process, system, function, state, organizational activity.